Ecological Index and Distribution Patterns of Seagrass in Banda Sea Tourism Park (TWP) - Dwi Rosalina; Awaluddin Awaluddin; Khairul Jamil; Agus Surachmat; Katarrina Hesty Rombe; Anisa Aulia Sabilah (Jurnal Kelautan, 2023)
ABSTRACTSeagrass beds have an important role as the main source of primary productivity or organic matter producers, habitat for various biota, nursery grounds, spawning grounds, food sources for rare biota, and support for the diversity of marine biota species, as well as the economic value of seagrass ecosystem services. This study aims to determine the ecological index and distribution pattern of seagrass in the Banda Sea Aquatic Tourism Park (TWP). The method used is a line transect with a quadrant size of 50 cm x 50 cm that is placed perpendicular to the shoreline. The results showed that the seagrass diversity index at the study site consisted of 7 types of seagrass, namely Thalassia hemprichii, Enhalus acoroides, Cymodocea rotundata, Cymodocea serrulata, Halodule uninervis, Halophila ovalis, and Syringodium isoetifilium. The diversity index is categorized as moderate with a value of H' = 0.01-0.05, and a uniformity value of 0.71 has a high uniformity, which means that the number of individual species from one species to another is not much different from a stable environmental condition. The distribution pattern of seagrass with Id 1 is a grouped category. The physicochemical parameters obtained were in accordance with the growth of seagrass life.Keywords: Banda sea, Distribution pattern, Diversity, Dominance, Seagrass, Uniformity